Eficácia da técnica dupla guiada comparada à técnica convencional no aumento de coroa estético: estudo clínico, controlado e randomizado - Carrera, Thaisa Macedo Iunes (2021)
The present study aims to compare the use of the guided dual technique with digital planning in the esthetic crown lengthening (ECL) with the conventional technique in relation to the stability of the gingival margin position and patient/specialist satisfaction. Twenty four patients diagnosed with altered passive eruption (APE) type I subcategory B were selected and divided into two groups. In control group (n = 12), the conventional ECL was planned by clinical examination and transgingival probe (TP); in test group (n = 12), patients were submitted to ECL using soft tissue cone-beam computed tomography (ST-CBCT), digital planning and guided dual technique. Clinical parameters were assessed clinically at baseline, immediately after the intervention (IAI), and 4, 8 and 12 months after the procedure. The participants and specialists were submitted to satisfaction questionnaires before and 8 months after ECL. Gingival display mean (GD) was reduced of 3.16 mm (±1.61) for 1.52 mm (±1.41) after 12 months in control group. In test group, GD was significantly reduced of 2.83 mm (±1.22) to 1.69 mm (±0.90) after 12 months. Clinical crown length mean (CCL) at baseline was 8.09 mm (±0.77) and increased significantly at IAI to 9.92 mm (±0.62) with minimal significantly reduction after 12 months (9.47 mm [±0.60]) in control group. Similarly, CCL at baseline was 8.04 mm (±0.69) and increased significantly at IAI to 9.94 mm (±0.57) with minimal reduction after 12 months (9.35 mm [±0.80]) in test group. No differences were found between CCL determined in the digital planning (9.59 mm [±0.64]), at IAI (9.94 mm [±0.57]) and after 12 months (9.35 mm [±0.80]). The overall correlations between measurements made in TP for anatomic crown length mean (ACL) (r=0.79) and cemento- enamel junction to bone cresct distance (CEJ-BC) (r=0.42) and the actual measurements made during the intervention were strong. For ST-CBCT analysis were verified a strong positive correlation between the estimated CCL (r=0.88) based on the ST-CBCT and the actual CCL measured in baseline. The correlation between ACL (r=-0.20), CEJ-CO (r=-0.54) and gingival thickness (GT) (r=-0.43) were not significant. No correlation was found between GT and gingival margin stability (r=-0.10). High esthetic satisfaction with dental and periodontal parameters was demonstrated by participants/specialists using VAS esthetic and questionnaires analysis without differences between groups. In conclusion, the dual guided technique was as effective as the conventional technique in APE treament with stable results after 12 months of follow-up.